Design of Dual-Band MIMO Array Antenna and Its Characterization for Urban Millimeter Wave Channel Conditions - B. G. Parveez Shariff; Tanweer Ali; Satish Kumar Sharma; Qammer H. Abbasi; Masood Ur-Rehman; Yahia M. M. Antar; Pradeep Kumar; Pallavi R. Mane; Sameena Pathan (IEEE Access, 2025)
The multiple-input-multiple-output (MIMO) antenna improves the channel capacity, and the array antenna improves the channel condition. A combined feature benefits the current cellular and other 5G applications. The strength of the MIMO array antenna is that it improves channel condition and operates with wide bandwidth and directional beam, achieving high gain. Not many of the articles focused on the second issue. Thus, this article focuses on designing a MIMO array antenna with a directional narrow beam resonating at dual bands that are 28 and 38 GHz. The circular slot in the ground plane serves a dual purpose: i) improve the bandwidth at both bands ranging from 25.35-30.53 GHz, and 36.76-41.43 GHz. ii) It acts as a decoupling structure providing isolation $\vert $ S $21\vert \gt 39$ dB and 42 dB in respective bands. The proposed antenna generates circular (RHCP) and elliptical (LHCP) polarization in the first and second bands. The antenna has achieved half-power beamwidth (HPBW) of 15° and 16.5° in the YZ-plane and a broad beam in the XZ-plane. The antenna is validated for diversity metrics, and the results are satisfactory. The MIMO antenna performance regarding channel capacity and path loss is virtually tested for cellular Picocell urban scenarios with line-of-sight (LOS) and non-line-of-sight (NLOS) conditions. The computed results agree with the analytical results of standard Friss, Stanford Inter-University (SUI), and Close-In (CI) models.